Pragmatic Paradigms in Professional Discourse: A Comparative Analysis of Speech Act Theory and Gricean Pragmatics (Al-Farooq Journal of Sciences, 2026)
This study presents a comparative analysis of Speech Act Theory (Austin, 1962; Searle, 1969) and Gricean Pragmatics (Grice, 1975) as frameworks for interpreting institutional workplace discourse. Using a naturally occurring transcribed interaction from the Hadfield Institute involving three administrative staff members, the paper evaluates the explanatory adequacy of each model in accounting for both the actional and inferential dimensions of professional communication. It is argued that Speech Act Theory provides superior analytical leverage for workplace interaction due to its capacity to account for the high frequency of directive illocutionary acts, explicit performatives, and institutionally conditioned power asymmetries that characterize task-oriented talk. In contrast, while Grice’s Cooperative Principle and conversational maxims offer valuable insights into inferential processes, their application to workplace data is limited by problems of maxim overlap, contextual indeterminacy, and a mismatch with the explicitness norms of professional settings (Thomas, 1995; Frederking, 2009). Through systematic coding of locutionary, illocutionary, and perlocutionary acts alongside observance and non-observance of Gricean maxims, this paper demonstrates that Speech Act Theory more effectively captures the functional, goal-driven nature of workplace language. Implications for discourse analysis, organizational communication training, and pragmatics pedagogy are discussed.
Keywords: Speech Act Theory, Gricean pragmatics, workplace discourse, directives, illocutionary acts, conversational implicature, institutional talk